Life threatening self starvation; a case report - Rodrigo, Chaturaka; Henegama, Thushani; Hanwella, Raveen (Springer Nature, 2013)
Background: Obsessive compulsive disorders are a complex group that can have a variety of manifestations. Many authors now describe an obsessive compulsive spectrum disorder where many other specific diagnostic entities such as trichotillomania, tic disorders and body dysmorphic disorder are considered to be related and linked disorders. Case presentation: We report a case of a twenty two year old Sri Lankan male who presented with life threatening self starvation due to severe obsessive compulsive disorder. The diagnosis was not considered till late due to the atypical presentation of the patient. While his symptoms bordered on a delusional psychosis, a decision was made to treat him as for obsessive compulsive disorder with behavioural therapy which was successful in the end. Conclusions: In analysis of a patient with severe anorexia, the psychological causes should not be forgotten. In fact, if the feeding pattern of the patient was observed at the beginning, unnecessary investigating and life threatening worsening of the condition could have been avoided
Keywords: Cognitive Behaviour Therapy; Celiac Disease; Obsessive Compulsive Disorder; Pathological Gambling; Tourette Syndrome